PENGARUH GOOD CORPORATE GOVERNANCE (GCG)TERHADAP KINERJA KEUANGAN PERUSAHAAN: Studi Empiris Per usahaan Manufaktur Sub Sektor Farmasi yang terdaftar Di Bursa Efek Indonesia Tahun 2017-2018 (STIE Rajawali Purworejo, 2021)
Economic developments in the business world are very fast and increasingly strong, resulting in demands for companies to continue to carry out various kinds of innovations to improve performance and expand company businesses so that they are able to compete and survive in the business world. Research with the title